ECM crosslinking enhances fibroblast growth and protects against matrix proteolysis in lung fibrosis - Philp, Christopher J.; Siebeke, Ivonne; Clements, Debbie; Miller, Suzanne; Hapgood, Anthony; John, Alison E.; Navaratnam, Vidya; Hubbard, Richard B.; Jenkins, Gisli; Johnson, Simon R. (American Thoracic Society, 2017)
Idiopathic pulmonary fibrosis (IPF) is characterised by accumulation of extra cellular matrix (ECM) proteins and fibroblast proliferation. ECM cross-linking enzymes have been implicated in fibrotic diseases and we hypothesised that the ECM in IPF is abnormally cross-linked which enhances fibroblast growth and resistance to normal ECM turnover. We used a combination of in vitro ECM preparations and in vivo assays to examine the expression of cross-linking enzymes and the effect of their inhibitors on fibroblast growth and ECM turnover. Lysyl oxidase like 1, 2, 3 and 4 were expressed equally in control and IPF derived fibroblasts. Transglutaminase 2 was more strongly expressed in IPF fibroblasts. Lysyl oxidase like 2, transglutaminase 2 and transglutaminase generated cross-links were strongly expressed in IPF lung tissue. Fibroblasts grown on IPF ECM had higher LOXL3 protein expression and transglutaminase activity compared with those grown on control ECM. IPF derived ECM also enhanced fibroblast adhesion and proliferation compared with control ECM. Inhibition of lysyl oxidase and transglutaminse activity during ECM formation affected ECM structure as visualised by electron microscopy and reduced the enhanced fibroblast adhesion and proliferation of IPF ECM to control levels. Inhibition of transglutaminase, but not lysyl oxidase activity, enhanced the turnover of ECM in vitro. In bleomycin treated mice, during the post-inflammatory fibrotic phase, inhibition of transglutaminases was associated with a reduction in whole lung collagen. Our findings suggest that the ECM in IPF may enhance pathological cross-linking which contributes to increased fibroblast growth, resistance to normal ECM turnover to drive lung fibrosis.